Fish species identification in canned pet food by BLAST and Forensically Informative Nucleotide Sequencing (FINS) analysis of short fragments of the mitochondrial 16s ribosomal RNA gene (16S rRNA). (April 2015) - Armani, A.; Tinacci, L.; Xiong, X.; Castigliego, L.; Gianfaldoni, D.; Guidi, A.
Abstract: Nowadays, pet food claiming high-valued fish among ingredients is largely available on the market. Unfortunately, the modifications induced by processing make species identification by visual inspection difficult and hinder the enforcement of the legislation on traceability. In this work, after aligning 819 sequences of Clupeidae, Engraulidae, Salangidae and Scombridae families, we developed new universal primers for the amplification and sequencing of 2 short fragments (±118 and ±213) of the mitochondrial 16s ribosomal RNA ( 16S rRNA ) gene. Once tested on 130 DNA reference samples, these primers were used in the analysis of highly degraded DNA extracted from 43 canned cat food containing whole minnows (whitebait) (M) and tuna, or bonito or mackerel fillets (F). Three M and 2 F samples were analyzed for each can. A BLAST and a FINS analysis, the latter performed only on the 118 bp fragment, were performed separately on the sequences obtained from M and F samples. All the M samples were identified at the species or genus level by both BLAST and FINS analysis. This allowed to highlight an impressive rate of mislabeling (100%). F samples, for which FINS was less performing in species identification, resulted mislabeled in 40% of the products. Highlights: Elite pet food with prized fish species is well regarded by pet-owners. Mislabeling may threaten fair trade and fish stock preservation. DNA-based analysis is often the only mean to verify species used as ingredients. We used new primers for PCR-sequencing analysis of the 16S rRNA gene in pet food. BLAST and FINS analysis highlighted a high rate of incorrect labeling.